Explainable AI for credit assessment in banks - Petter Eilif de Lange; Borger Melsom; Christian Bakke Vennerød; Sjur Westgaard (Journal of Risk and Financial Management, 2022)
Banks' credit scoring models are required by financial authorities to be explainable. This paper proposes an explainable artificial intelligence (XAI) model for predicting credit default on a unique dataset of unsecured consumer loans provided by a Norwegian bank. We combined a LightGBM model with SHAP, which enables the interpretation of explanatory variables affecting the predictions. The LightGBM model clearly outperforms the bank's actual credit scoring model (Logistic Regression). We found that the most important explanatory variables for predicting default in the LightGBM model are the volatility of utilized credit balance, remaining credit in percentage of total credit and the duration of the customer relationship. Our main contribution is the implementation of XAI methods in banking, exploring how these methods can be applied to improve the interpretability and reliability of state-of-the-art AI models. We also suggest a method for analyzing the potential economic value of an improved credit scoring model.
Keywords: G17; G21; 650; credit default prediction; credit risk modelling; explainable artificial intelligence (XAI); Light Gradient Boosting Machine (LightGBM)